Nitrogen-doped porous graphene with surface decorated MnO2 nanowires as a high-performance anode material for lithium-ion batteries. Issue 19 (8th March 2016) - Jiang, Cheng; Yuan, Chenpei; Li, Peihang; Wang, Heng-guo; Li, Yanhui; Duan, Qian
Abstract : Nitrogen-doped porous graphene with surface decorated MnO2 nanowires is used as a high-performance anode material for lithium-ion batteries. Abstract : An effective strategy was developed to prepare a unique composite by growing MnO2 nanowires on the surface of nitrogen-doped porous graphene (MNPG). The nitrogen-doped porous graphene (NPG) can not only be used as a conductive matrix to greatly improve the conductivity of the MnO2 nanowires but also serve as the active material contributing lithium storage capacity to the composite. As expected, when evaluated as an anode material for lithium-ion batteries (LIBs), the MNPGs show a highly stable capacity of up to 1132.4 mA h g −1 after 300 cycles at 0.1 A g −1, a capacity higher than 300 mA h g −1 even after 2400 cycles at 1 A g −1 and a good rate capability of 248.5 mA h g −1 even at 10 A g −1, which might open new avenues for the design of high-performance electrode materials.